Analysis of Disaster Resilience Governance in Pancoh Tourist Village, Yogyakarta - Suryani, Dewi Amanatun; Suyatno, Suyatno (Journal of Social Politics and Governance (JSPG), 2023)
Mount Merapi, an active volcano, poses constant threats to the surrounding communities. Pancoh, a village located 9.6 km away, has embraced resilience efforts in response to the eruption in 2010. This research aims to explore the community's preparedness, disaster risk management strategies, and investments in disaster risk reduction, focusing on the development of sustainable ecotourism. A qualitative descriptive approach was employed for this study. The research findings reveal that resilience initiatives in Pancoh Tourism Village commenced after the 2010 eruption of Mount Merapi. Disaster risk management is achieved through the promotion of sustainable ecotourism. The research concludes that Pancoh Tourism Village has made commendable progress in building resilience since the Mount Merapi eruption in 2010. The integration of sustainable ecotourism, community involvement, and investments in disaster risk reduction showcases a holistic approach to mitigating the impact of volcanic disasters.